2016
DOI: 10.18689/mjnn-1000101
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of the PVA Nanofibers produced by Electrospinning

Abstract: Electrospinning is a simple and quick technique for producing fibers with nanoscale diameters from a wide range of materials. The Polyvinylalcohol PVA Polymer dissolved in the DMF was electrospun to obtain the alignment nanofibers PVA. The nanofibers were obtained using 25 wt% solution concentration, an applied voltage 10 kV, spinning distance10 cm and different flow rates of 0.1, 0.2, and 0.3 ml/hr. The properties of alignment nanofibres including morphology, crystallization, functional group and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…For the pure PVA polymer (curve b), the FT‐IR characteristics peak was observed at 3,300 cm −1 showing the OH stretching and the peaks at 2900 cm −1 shows the symmetric and asymmetric stretching of CH 2. 26 For pure PMMA polymer, stretching vibrations can be seen at 3,000–2,900 cm −1 , and the peak at 1,750 cm −1 shows the presence of carbonyl group (curve d). Addition of CPX in the individual nanofibers mat of PVA (curve c), PMMA (curve e) and composite PVA:PMMA (curve f) shows the disappearance of the CPX peaks showing that the drug is completely encapsulated in the polymer matrix.…”
Section: Resultsmentioning
confidence: 98%
“…For the pure PVA polymer (curve b), the FT‐IR characteristics peak was observed at 3,300 cm −1 showing the OH stretching and the peaks at 2900 cm −1 shows the symmetric and asymmetric stretching of CH 2. 26 For pure PMMA polymer, stretching vibrations can be seen at 3,000–2,900 cm −1 , and the peak at 1,750 cm −1 shows the presence of carbonyl group (curve d). Addition of CPX in the individual nanofibers mat of PVA (curve c), PMMA (curve e) and composite PVA:PMMA (curve f) shows the disappearance of the CPX peaks showing that the drug is completely encapsulated in the polymer matrix.…”
Section: Resultsmentioning
confidence: 98%
“…The FTIR spectrum of blank nanofibrous film represented absorption peaks at 3290 cm −1 that referred to the O–H stretching vibration of the hydroxyl group of the base polymer. The peaks at 1444 and 2944 cm −1 referred to –CH 2 bending and C–H stretching of PVA, respectively [ 47 , 48 ]. The absorption peaks at 1696 cm −1 referred to C=O from the amide group of PVP [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on those images, it is evident that the diameter of the produced fiber is within the range of 10 nm and 500 nm. Several preliminary studies have also reported its size range [24] , [25] , [26] , [27] . Fig.…”
Section: Validation and Characterizationmentioning
confidence: 99%